Effect of Trehalose and Sucrose on the Hydration and Dipole Potential of Lipid Bilayers - Luzardo Lorenzo, María del Carmen (2000)
The water activity in dimyristoylphosphatidylcholine (DMPC) decreases by 60% when the lipid is dehydrated in the presence of trehalose concentrations higher than 0.02 M. In contrast, sucrose in concentrations 10 times higher produced only a 20% decrease in the water activity in the sample. Titrations of a DMPC solution in chloroform yielded 14 water molecules per lipid when pure water was added and seven water molecules per lipid when the titration was done with 0.025 M trehalose. The same concentrations of sucrose produced a turbid solution, which made it impossible to quantify the number of water molecules per lipid. Lipid monolayers spread on an air/water interface showed a decrease from 480 mV in pure water to 425 mV in 0.1 M trehalose. However, the same concentrations of sucrose produced an increase of less than 100 mV. Results obtained with Fourier transform infrared spectroscopy (FTIR) under the same conditions denoted that trehalose binds to the carbonyl groups, while sucrose showed no specific binding. It is concluded that per lipid molecule, 11 of 14 water molecules can be replaced by three trehalose molecules. About four are displaced by changes in the water activity of the bulk solution, and seven by specific interactions with the phospholipids. In this last case, at least two of them are linked to the carbonyls, and this appears to be the cause of the decrease in the dipole potential of the membrane. In contrast, four sucrose molecules displace only three water molecules per lipid, with no effect on the dipole potential or the carbonyl groups.